Histomorphometric analysis of the healing process after the replantation of rat teeth maintained in bovine milk whey and whole milk - Corrêa, Ana Paula S. [UNESP]; Ferreira, Pedro Henrique S. G. [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Kooji [UNESP]; Caliente, Eliana A. [UNESP]; Poi, Wilson R. [UNESP] (Wiley, 2017)
Background/Aim: In cases of tooth avulsion, a minimal extra-alveolar dry storage period or the use of a suitable storage medium is crucial to maintaining the vitality of the periodontal ligament. Whey has similar properties to milk and has therefore been investigated as a storage medium for avulsed teeth. The aim of this study was to evaluate the repair process after replantation of rat teeth kept in whey and whole milk. Materials and Methods: Thirty-six male rats were divided into four groups of nine animals. The upper right incisor was extracted under general anesthesia. In Group I, the teeth were immediately replanted without treatment (positive control). In Group II, the teeth were stored in 50 mL of sweet whey. In Group III, the teeth were kept in 50 mL of long-shelf-life whole milk (UHT, Parmalat®). In Group IV, the teeth were kept dry (negative control). After 60 minutes, the teeth in Groups II, III, and IV were replanted into their sockets. The animals were subjected to euthanasia 60 days after replantation. The specimens were stained with hematoxylin and eosin for histomorphometric analysis. Results: The organization of the periodontal ligament in Group II (whey) was similar to that in Groups I (immediate replantation) and III (whole milk) (P >.05). However, some specimens in this group exhibited periodontal fibers inserted into the bone and cementum throughout the entire length of the periodontal ligament. This occurred in the group submitted to immediate replantation, whereas this histological aspect was not seen in whole milk group. Group IV (late replantation) had a higher rate of root resorption. Regarding the root repair process, it was expected that Group I (immediate) would demonstrate more favorable repair than the other groups. However, Group III (whole milk) had better results when compared to Groups II (whey) and IV (late) (P <.05). Conclusion: Whey and whole milk achieved similar results and were adequate storage media for avulsed teeth.
Keywords: tooth avulsion; tooth replantation; traumatology